2018
DOI: 10.1111/joss.12317
|View full text |Cite
|
Sign up to set email alerts
|

Children and adults' sensory and hedonic perception of added sugar reduction in grape nectar

Abstract: Reducing the added sugar content of sugar‐sweetened beverages is one of the most cost‐effective strategies to achieve short‐term changes in added sugar intake. The present study aimed at evaluating children and adults' sensory and hedonic perception of added sugar reduction in grape nectar. For this purpose, two studies were carried out. In the first study, five sequential difference thresholds for added sugar in grape nectar were determined with school‐aged children and adults using paired comparisons. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 50 publications
0
12
0
1
Order By: Relevance
“…These findings are in line with those reported by Schouteten, De Steur, et al () who examined the possibility of using the CATA response format to obtain discriminatory sensory profiles for speculoos biscuits with a child and teenage population. Furthermore, studies working with children and teenagers showed that the CATA response format is able to obtain distinguished sensory profiles for powdered fruit‐flavored juices (Cardinal et al, ), milk desserts (Vidal et al, ), fiber‐enriched apple purees (Laureati et al, ), and grape nectar (Lima, Ares, & Deliza, ).…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in line with those reported by Schouteten, De Steur, et al () who examined the possibility of using the CATA response format to obtain discriminatory sensory profiles for speculoos biscuits with a child and teenage population. Furthermore, studies working with children and teenagers showed that the CATA response format is able to obtain distinguished sensory profiles for powdered fruit‐flavored juices (Cardinal et al, ), milk desserts (Vidal et al, ), fiber‐enriched apple purees (Laureati et al, ), and grape nectar (Lima, Ares, & Deliza, ).…”
Section: Discussionmentioning
confidence: 99%
“…The association of the FSOJ sample with the term health can be explained by the popular knowledge that orange juice consumption provides health benefits. According to Rodrigues et al () and Lima et al (), health benefits were the most important aspect in food evaluation for consumers.…”
Section: Resultsmentioning
confidence: 99%
“…According to Rodrigues et al (2017) and Lima et al (2018), health benefits were the most important aspect in food evaluation for consumers.…”
Section: For Windows Version 2016 (Microsoft)mentioning
confidence: 99%
See 1 more Smart Citation
“…These products have different concentrations of natural orange juice, varying from 100% (NFC, UHT) to 1–2% (PDM). Moreover, water, sugar and food additives (pigments, preservatives, gums, and noncaloric sweeteners) are added to some of them, which makes them cheaper than 100% fruit juices and more accessible to consumers (Lima, Ares, & Deliza, ; Longo‐Silva et al, ).…”
Section: Introductionmentioning
confidence: 99%